ANALISIS PREMI TAHUNAN INDIVIDU DENGAN MANFAAT YANG DIBAYARKAN PADA AKHIR TAHUN KEMATIAN - Krishna Prafidya Romantica; Paiz Jalaludin (JURNAL LENTERA AKUNTANSI, 2024)
Life insurance is an insurance product that provides guarantees in the form of benefits to the insured's family if the insured dies in the future. The amount of this benefit is influenced by the amount of the annual premium paid by the insurer to the insured. The researcher will calculate the amount of the individual's annual premium on endowment insurance. The researcher will use a fixed interest rate to calculate the discount factor and the Gompertz distribution approach to calculate the insurer's chance of survival. Previously, the researcher will estimate the Gompertz distribution parameters using the Maximum Likelihood Method (MLE) based on the 2011 Indonesian Mortality Table (female). Furthermore, the researcher will calculate the insurer's chance of survival using the Gompertz distribution to obtain the actuarial present value of the initial term annuity and the actuarial present value of the endowment life insurance. In addition, the researcher will calculate the comparison of the present value of the endowment life insurance to the present value of the life annuity. The last step is that the researcher will multiply the comparison of this present value by the benefits received to calculate the amount of the individual's annual premium. The calculation results show that the comparison of the present value of dual-purpose life insurance to the present value of a living annuity is getting smaller as the policy coverage period increases. As a result, the amount of the individual's annual premium will also be smaller. This shows that the amount of the annual premium is influenced by interest rate factors, the insurer's life chances, and the length of the coverage period.